Endomikoriza yang Berasosiasi dengan Tanaman Pertanian Non-legum di Lahan Pertanian Daerah Transmigrasi Koya Barat, Kota Jayapura - Supeni Sufaati; Suharno suharno; Iriandi H. Bone (Jurusan Biologi FMIPA Universitas Cenderawasih, 2011)
Endomycorrhiza palys important role in nutrient uptake of agricultural plant. The purpose of this study was to investigate the presence of endomycorrhiza associated with non-legume plants, i.e.:Zea mays L., Solanum lycopersicum L., Capsicum frutescens L., Brassica oleracea L. and Brassica juncea (L.) Czern, in agricultural area in Koya Barat, Jayapura. Survey was done before collecting root and soil samples. The root of those non-legume plants were cleaned and stained using method developed by Kormanic and Mc.Graw. Wet seaving method was done to analyze soil samples. The result showed that those non-legume plants were infected by endomycorrhiza. The highest infection percentage was on corn (Zea mays L.), while the lowest was on cabbage (Brassica oleracea L.). Furthermore, from spore identification, 14 species of endomycorrhiza were found on the rhizosphere of those plants which were grouped into genus Glomus (5 species), Gigaspora (2 species), Acaulospora (2 species) and Scutelospora (1), however 4 species were remain unidentified yet. Therefore further study should be done to elucidate this problem.Key words: endomycorhiza, exploration, non-legum, Koya Barat, Jayapura.